2019
DOI: 10.1016/j.socscimed.2019.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Moral discourse in general practitioners’ accounts of obesity communication

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…We also built on existing literature that had highlighted that clinicians may not always stigmatise individuals but find it hard to negotiate stigma when advocating weight loss 61 . Our study also complemented literature 62 which noted the impact of weight stigma on patients' care, finding that experiences of perceived substandard care may cause avoidance of care, poor adherence to weight management interventions and distrust of clinicians.…”
Section: Discussionmentioning
confidence: 84%
“…We also built on existing literature that had highlighted that clinicians may not always stigmatise individuals but find it hard to negotiate stigma when advocating weight loss 61 . Our study also complemented literature 62 which noted the impact of weight stigma on patients' care, finding that experiences of perceived substandard care may cause avoidance of care, poor adherence to weight management interventions and distrust of clinicians.…”
Section: Discussionmentioning
confidence: 84%
“…Examples include lack of time or competing priorities, knowledge of obesity guidelines or relevant training, concerns of sensitivity or negative consequences (e.g. upsetting patients), and scepticism about the efficacy of advice [22,23,[44][45][46][47][48][49][50][51]. Similar themes have also been reported in patient-focused research [20,21,31].…”
Section: Discussionmentioning
confidence: 90%
“…For example, research with patients has suggested that perceived simplistic advice around consumption and exercise, the two forms of advice provided most frequently in this study, may have limited resonance with some patients [31]. Finally, it is possible that differences in weight management practice between GPs and PNs, and the barriers reported elsewhere [44][45][46][47][48][49][50][51], may relate to inherent differences in their professional roles, responsibilities, and nature of patient contact. It may, therefore, be beneficial for research to further examine PN and GPs separately to examine best practice, barriers, and opportunities for focussed interventions among each group.…”
Section: Discussionmentioning
confidence: 96%
“…The ideas for the existence of moral models in various social groups can find of Benjamin Grant Purzycki, Anne C. Pisor, Coren Apicella, Quentin Atkinson and Dimitris Xygalatas [7]. Quite a lot of research has been devoted to the study of moral discourse in various professional corporations, for example, the Maxine Blackburn and Afroditi Stathi medical corporations [8]. Since the Internet and integrated into it social networks have wide access to them, it is quite logical to use scientific studies on the moral postulates of the media, for example, works by Bradley Wilson [9], when studying moral aspects of behavior in social networks.…”
Section: Introductionmentioning
confidence: 99%